2022
DOI: 10.1155/2022/5210870
|View full text |Cite
|
Sign up to set email alerts
|

The Imbalance of Mitochondrial Homeostasis of Peripheral Blood-Derived Macrophages Mediated by MAFLD May Impair the Walking Ability of Elderly Patients with Osteopenia

Abstract: Introduction. Many Asian cohort studies have shown that nonalcoholic fatty liver disease (NAFLD), now renamed as metabolic dysfunction-associated fatty liver disease (MAFLD), increases the risk of osteoporosis, yet the effect of MAFLD on elderly patients with osteopenia (OPe) has not been reported. Objective. This study aimed to explore the influence of MAFLD on the function of macrophages in patients with OPe. Methods. A total of 107 elderly OPe patients with or without MAFLD who visited the Huadong Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Further research into skeletal biology, relevant molecular mechanisms, and signaling networks will provide important insights into addressing PMOP and its associated fragility fractures and uncovering novel therapeutic approaches [23]. Previous studies have demonstrated that the osteogenic microenvironment is crucial for maintaining the health and balance of bone tissue, and disturbances in the osteogenic microenvironment may lead to decreased bone formation and increased bone resorption, ultimately resulting in the development of PMOP [24]. Therefore, studying and modulating the osteogenic microenvironment is of signi cant importance for the prevention and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further research into skeletal biology, relevant molecular mechanisms, and signaling networks will provide important insights into addressing PMOP and its associated fragility fractures and uncovering novel therapeutic approaches [23]. Previous studies have demonstrated that the osteogenic microenvironment is crucial for maintaining the health and balance of bone tissue, and disturbances in the osteogenic microenvironment may lead to decreased bone formation and increased bone resorption, ultimately resulting in the development of PMOP [24]. Therefore, studying and modulating the osteogenic microenvironment is of signi cant importance for the prevention and treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…This causes causing severe physical, mental, and economic burdens to the patients. Previous studies have shown that the immune microenvironment may play an important role in the occurrence and development of OP ( 4 , 11 , 46 ). However, the specific targets and therapeutic mechanisms of OP remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They are functionally linked, and the infiltration of immune cells plays a vital role in the occurrence and development of OP ( 10 ). Factors such as the balance between Th1/Th2/Treg cells ( 3 ), inflammatory T cells (Th17) ( 4 , 10 ), regulatory B cells (Bregs) ( 4 ), and macrophages ( 11 ) play an important role in regulating osteoblasts and osteoclast homeostasis, which in turn affects osteoporosis ( 12 ). Regarding the immune system, assessing the varying degrees of immune cell infiltration and identifying the compositional differences in the infiltrating immune cells can help elucidate the molecular pathological mechanism of OP and develop new immunotherapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Due to its high global prevalence, it poses a serious threat to human health and a huge economic burden to society. 6 Steatosis is a reversible condition in its early stages and can be addressed through behavioural changes. 7 8 For example, increasing physical activity and controlling energy intake are particularly effective interventions in the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%